RhII‐Catalyzed De‐symmetrization of Ethane‐1, 2‐dithiol and Propane‐1, 3‐dithiol Yields Metallo‐β‐lactamase Inhibitors. (3rd August 2021) - Krasavin, Mikhail; Zhukovsky, Daniil; Solovyev, Igor; Barkhatova, Darina; Dar'in, Dmitry; Frank, Denia; Martinelli, Giada; Weizel, Lilia; Proschak, Anna; Rotter, Marco; Kramer, Jan S.; Brunst, Steffen; et al.
Abstract: Diversity‐oriented synthesis (DOS) is a rich source for novel lead structures in Medicinal Chemistry. In this study, we present a DOS‐compatible method for synthesis of compounds bearing a free thiol moiety. The procedure relies on Rh(II)‐catalyzed coupling of dithiols to diazo building blocks. The synthetized library was probed against metallo‐β‐lactamases (MBLs) NDM‐1 and VIM‐1. Biochemical and biological evaluation led to identification of novel potent MBL inhibitors with antibiotic adjuvant activity. Abstract : Thiols are potent inhibitors of metallo‐β‐lactamases, major resistance factors in Gram‐negative bacteria. Rh(II)‐based coupling procedure of dithiols to diazo building blocks was adopted for diversity‐oriented synthesis of a library of metallo‐β‐lactamase inhibitors. Most potent compounds displayed nanomolar potency and activity in multiresistent clinical isolates.